The Role of Self-compassion and Hope in the Relationship Between Psychological Wellbeing, Maladaptive Schemas, Resilience, and Social Support in Women With Multiple Sclerosis - Seyedeh Fatemeh Hassani; Taher Tizdast; Mohammad Reza Zarbakhsh (Iran University of Medical Sciences, 2021)
Background: Psychological disorders often threaten the mental health of individuals with Multiple Sclerosis (MS). Higher levels of psychological wellbeing and life satisfaction provide these patients with better social relationships and greater biopsychological health. The present study aimed to investigate the relationship between psychological wellbeing, early maladaptive schemas, resilience and perceived social support mediated by self-compassion and hope in women with MS. Methods: This descriptive-correlational study was conducted from August to October 2019. The study population consisted of all female patients with MS who were admitted to Imam Khomeini Hospital Complex, Milad Hospital, and Charity Foundation for Special Diseases in Tehran City, Iran. Using the stratification convenience sampling method, 300 patients were recruited as the study sample. The research instruments included the Self-Compassion Scale, Early Maladaptive Schema Questionnaire-Short Form, the Connor-Davidson Resilience Scale, the Multidimensional Perceived Social Support Scale, Ryff's Scale of Psychological Wellbeing, and the Adult Hope Scale. The collected data were analyzed by structural equation modeling. SPSS and AMOS were used for analyzing the collected data. Results: There was a positive and significant relationship between self-compassion, hope, resilience, perceived social support, and psychological wellbeing (P<0.01). There was also a negative relationship between early maladaptive schemas and psychological wellbeing in the study participants (P<0.01). The indirect path analysis data indicated that self-compassion and hope played a mediating role in the relationship between perceived social support, resilience, early maladaptive schemas, and psychological wellbeing (P<0.01). Conclusion: The designed model fitted the empirical data very well. Therefore, the research components can help researchers, therapists, and psychiatric nurses to design better procedures to care for patients with MS.